Characteristics of the skills of caregivers of people with dementia: observational study - Marie-Conception Leocadie; Jean-Manuel Morvillers; Sophie Pautex; Monique Rothan-Tondeur (BMC Family Practice, 2020)
Abstract Background Due to demographic change within an aging population as announced by the WHO, the involvement of caregivers is essential. Caregivers are required to change their roles within the family unit. Such life transitions experienced by caregivers to people confronted with dementia-type pathologies are sometimes difficult, necessitating the acquisition and development of certain skills. Few studies have shown that caregivers develop specific and essential skills to promote quality care and safety. To characterize their skills, there is a need to identify the abilities, knowledge, resources, obstacles and constraints that contribute to caregivers’ transitions. The research question for this study was: What skills do caregivers use to care for their loved one with dementia? Methods Qualitative observational research based on the epistemological paradigm of socioconstructivist knowledge was conducted. The study was carried out in the canton of Geneva and recruitment was carried out through the participation of the Alzheimer’s association and the association for the support and assistance of elderly people in medical and social institutions and their families (APAF). Observations and semi-structured interviews were conducted in the homes of 14 family carers caring for their loved one with dementia. The observations were transcribed on observation grids and the interviews were recorded. Subsequently, according to the classic distinction of Denzin (Interpretive interractionism, 2001), we analysed the observation notes and verbatims, then as recommended by Miles et al. (Qualitative data analysis: a methods sourcebook, 2014), two researchers triangulated the results. Results The results identified five types of situations regularly experienced by caregivers. The study characterized 11 skills that caregivers use to cope with their daily lives. The learning process and maladaptive behaviours in caring for their loved ones with dementia were also highlighted. Conclusion This study was able to point out that today’s caregivers have developed more competency than their predecessors. This evolution can be explained by new paradigms of care requiring caregivers to be more involved. Although some caregivers need training, others through their experiences can act upon and provide knowledge. To improve the quality and safety of care for people with dementia, this expertise can be the subject of partnerships between caregivers and health care staff.